Distributed Computing and Networking 12th International Conference, ICDCN 2011, Bangalore, India, January 2-5, 2011, Proceedings - Aguilera, Marcos K.; Yu, Haifeng; Vaidya, Nitin H.; Srinivasan, Vikram; Choudhury, Romit Roy (Theoretical Computer Science and General Issues, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Distributed Computing and Networking, ICDCN 2011, held in Bangalore, India, during January 2-5, 2011. The 31 revised full papers and 3 revised short papers presented together with 3 invited lectures were carefully reviewed and selected from 140 submissions. The papers address all current issues in the field of distributed computing and networking. Being a leading forum for researchers and practitioners to exchange ideas and share best practices, ICDCN also serves as a forum for PhD students to share their research ideas and get quality feedback from the well-renowned experts in the field.